A case of mother-daughter relationship with five inconsistencies with hereditary pattern out of 56 autosomal short tandem repeat markers. Issue 1 (December 2019) - Liu, Ying; Zhang, Jingjing; Liu, Jiajia; Liu, Yacheng; Yan, Jiangwei
Highlights: Five out of 56 autosomal STR loci were found to be inconsistent with Mendelian inheritance in this maternity testing of Duos. The total of 56 autosomal STR loci, 86 autosomal SNPs, 19 X-STRs and the whole mitochondrial genome were detected by capillary electrophoresis (CE) and Next-generation sequencing (NGS). It was meaningful for forensic practice. Abstract: The maternity testing was performed for two individuals whom are suspected mother and daughter. A total of 56 autosomal STR loci, 86 autosomal SNPs, 19 X-STRs, and the entire mitochondrial genomes were analyzed by capillary electrophoresis (CE) and Next-generation sequencing (NGS). In this case, it was confirmed that 51 out of 56 autosomal STR loci and 86 autosomal SNPs were consistent with Mendelian inheritance, but there were five STR loci not complied with the inheritance pattern. Further, 19 X-chromosome STR loci and the mitochondrial genome sequences of both individuals conformed to the inheritance pattern. For testing analysis, the unconventional statistical methods were adopted on the case results. Based on the results, it was concluded that the relationship of these two individuals was mother and daughter.